Pengetahuan dan Kesiapan Kehidupan Berkeluarga Bagi Remaja: Studi Komparatif di SMA, SMK dan MA - Nining Tunggal Sri Sunarti; Isabela Rahmawati Rahmawati (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2022)
ABSTRACT Background: Cases of early marriage is still high in Indonesia, including in the district of Bantul. This study aims to determine differences in knowledge and readiness of family life for young people in SMA, SMK and MA in Bantul in the year 2015. Method: The study used observational analytic design with cross sectional approach. The study was conducted in Senior Hight Schools on the district of Bantul. Number of samples 3 groups, each group a total of 68 respondents. Univariate analysis used frequency distribution, bivariate analysis used Mann Whitney test and multivariate analysis uses kruskal wallis. Result: The results showed that the majority of students aged 16 years and generally do not know about the ICRS. Results of multivariate analysis with the Kruskal showed no difference in knowledge about the readiness of life for adolescents at SMA, MA and SMK (P = 0.001), and there are differences in readiness life for adolescents at SMA, MA and SMK (P = 0.002). It was concluded that there are differences in knowledge about the readiness of life for adolescents in high school, MA, and SMK and there are differences in readiness life for adolescents in high school, MA, and SMK. Required overall effort to improve the knowledge and readiness teens about family life. Keywords: knowledge, readiness, family readiness, adolescents